Resposta :
[tex]x^2+3x-10=0[/tex]
[tex]x=\frac{-3 \pm \sqrt{3^2-4 \times 1 \times (-10)} }{2 \times 1}[/tex]
[tex]x=\frac{-3 \pm \sqrt{49} }{2}[/tex]
[tex]x=\frac{-3 \pm 7}{2}[/tex]
[tex]x_1 = \frac{-3+7}{ 2}=2\\x_2=\frac{-3-7}{2}=-5[/tex]
![Ver imagem HATINH](https://pt-static.z-dn.net/files/df3/349fb46aeb50e3764f6340a09143a4e9.jpg)
[tex]x^2+3x-10=0[/tex]
[tex]x=\frac{-3 \pm \sqrt{3^2-4 \times 1 \times (-10)} }{2 \times 1}[/tex]
[tex]x=\frac{-3 \pm \sqrt{49} }{2}[/tex]
[tex]x=\frac{-3 \pm 7}{2}[/tex]
[tex]x_1 = \frac{-3+7}{ 2}=2\\x_2=\frac{-3-7}{2}=-5[/tex]